DEVELOPING PROMPTS OF ARGUMENTATIVE ESSAY WRITING FOR EFL COLLEGE STUDENTS - Teguh Budiharso (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2017)
Assessment of essay writing varies in product oriented, primary trait scoring system, and process oriented.  This study examines how rubric in argumentative essay writing are developed. The findings emphasized that essay writing focused on the argumentative essay. Models of essay utilized for TOEFL test are considerably suggested for the topics.  In addition, descriptors of the essay elaborated for standard assessment refer to characteristics of a good paragraph outlining: topic sentence and controlling ideas, developing sentences, and concluding sentence; and those for essay writing would emphasize on introductory paragraph whose thesis statement is included in the paragraph, developing paragraphs for details, and concluding paragraph.